Effect of different plot coverings on emergence and early development of seven palm species (arecaceae) - Môro, Fabíola V. [UNESP]; Taveira, Leontino R. [UNESP]; Bieras, Ângela C. [UNESP]; Marcon, Victor M. [UNESP]; Silva, Marco A. S. [UNESP]; Filho, Carlos F. Damião [UNESP]; Môro, José R. [UNESP] (My University, 1999)
The Arecaceae family comprises plants with economical importance in many Brazilian regions, for agricultural exploration or for landscaping. In great portion, species of this family present low germination velocity and percentage. This work meant to evaluate the germination and early development of seven palm species (Archontophoenix alexandrae H. Wendl. et Drude, Copernicia prunifera (Miller) H.E. Moore, Latania commersonii Gmel., Livistona chinensis R. Br., Syagrus campos-portoana Bondar, Syagrus coronata (Mart.) Beccari, Syagrus picrophylla Barb. Rod.), submitted to three kinds of seed bed plot coverings. Three 10 x 2 m seedbeds were built and filled with a mixture of sand, soil and chicken manure (1:3:0.5 proportion), where two lines were sown with each specie. On top of each seedbed, plastic covering and fifty percent screen were set allowing one third of the seedbed to full sunlight exposure. Seedbeds were irrigated by dripping system. All species had the same germination rate, regardless of the covering, by the end of the experiment (146 days after sowing), eventhough, A. alexandrae under plastic covering conditions, L. commersonii at full sunlight exposure and Syagrus campos-portoana under fifty percent shade, had reached that percentage around 51 days after sowing. The remaining species reached the greatest germination percentage earlier with some of the coverings, rather than at full sunlight exposure. For the studied conditions, covering type had no effect in leaf length and width. For leaf number, there was interaction between species x covering type for Livistona chinensis and Copernicia prunifera.
Keywords: Archontophoenix alexandrae; Copernicia prunifera; Germination velocity; Latania commersonii; Livistona chinensis; Syagrus campos-portoana; Syagrus cownata; Syagrus picrophylla